Protecting environmental justice in light of developmental agendas: the case of laps set Lamu port. - MANYARA, WAIRIMU (Strathmore University, 2021)
Kenya has widely publicized its development agenda and it has been at the forefront of political campaigns under the auspices of projects such as Vision 2030. One of the biggest development projects that the state has undertaken has been the LAPSETT Project. From the onset of the project, there have been several concerns regarding the effects of the project on Lamu given the fact that the island is a World Heritage protected site. It is hence essential to investigate the environmental protection mechanisms in place in the Kenyan legal framework which would secure the interests of Lamu County and its communities.
Environmental justice is espoused as one of the methods to ensure the balancing of rights between competing interest of development and environmental preservation. This conflict comes as there are several environmental commitments and obligations that are placed on the state while there still anthropogenic needs such as development in need of being realised. LAPSETT in this case poses the dilemma as it is projected to manifest exponential benefits while concurrently impacting community and even environmental rights.